Zagreb during World War I: Historic newspapers as source for social history research - Mirjana Jurić (Libellarium: Journal for the Research of Writing, Books, and Cultural Heritage Institutions, 2009)
The aim of the paper is to reconstruct the social image of Zagreb during World War I by focusing on the influence of war circumstances on urban life, the living conditions and the position of children as the most vulnerable group of inhabitants, by using primarily newspapers as historical sources. In order to achieve as complete an image as possible, various publications were used (‘Narodne novine’, ‘Jutarnji list’, ‘Obzor’, ‘Novine’, ‘Hrvatska’, ‘Ilustrovani list’, ‘Katolički list’ and ‘Narodna zaštita’) which proved to be an inexhaustible source of information and contemporary observations on the above-mentioned issues. The paper tells about the general sense of insecurity in the city during wartime, the usual war motives (the wounded in the streets, life under war regulations, forced charity events) and the consequences of the war situation (shortage of living supplies and poverty, begging and vagrancy, neglected children and war orphans). The paper has proven that historic newspapers are a first-class historical source. The essential scientific contribution of the paper is the reconstruction of part of Zagreb social history during World War I, highlighting that this part of Croatian history has still been poorly and incompletely researched.